A Green and Sustainable Approach for Converting Laboratory Latex Glove Waste into Liquid Fuel via Microwave-assisted Pyrolysis - Wangsa, Wangsa; Saviola, Aldino Javier; Hauli, Latifah; Trisunaryanti, Wega; Chandra, Patrik; Fitria, Riska Astin; Mahayuwati, Puspa Nindro; Wijaya, Karna (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The extensive use of chemical laboratories for experimental and research activities has resulted in the substantial accumulation of latex glove waste, a widely used form of personal protective equipment (PPE). This study presents a novel and sustainable approach for converting laboratory latex glove waste into liquid fuel using microwave-assisted pyrolysis (MAP), which aligns with the principles of green chemistry. Under optimal conditions, including a microwave power of 800 W and an irradiation time of 30 min, the process achieved a liquid product yield of 52.58 wt%, with 41.86 wt% consisting of gasoline-range hydrocarbons (C₅–C₁₂). The primary compound identified in the liquid product was D-limonene (C₁₀H₁₆), a valuable monocyclic terpene. Compared to conventional pyrolysis conducted in a semi-batch reactor, the MAP process exhibited superior performance in terms of liquid yield, gasoline-range hydrocarbon content, total hydrocarbon composition, and calorific value. This innovative waste-to-fuel conversion method demonstrates the strong potential of MAP as an efficient and environmentally responsible strategy for waste valorization and resource recovery. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).